BLE Beacon-based Etiquette System of Smart Devices - Keum, Ki-mun; Jang, Chang-bok; Kim, Ki-Bong Kim; Kwon, Ohseok (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, smartphones has become necessary electronic devices to use the various mobile services in everyday life. Rude uses of smartphones cause many troubles such as invasions of others privacy and rights.Methods/Statistical analysis: For these reasons, smartphones are controlled in a variety of ways via the compulsory collection and the smartphone regulation service, but these methods have side effects such as infringing individual rights due to excessive smartphone usage restriction and control.Findings: Therefore, it is necessary to switch to a more positive etiquette service than the service centered on the usage regulation, and to have a social mobile etiquette service for mutual respect among members of society. We propose public etiquette services of smartphone which use BLE (Bluetooth Low Energy) Beacons to show the rules of etiquette and set your smartphone to etiquette mode. We are very confident that BLE beacons are suitable devices to determine the scope of etiquette service indoors because BLE signals are at the core of the indoor location technology.Improvements/Applications: This paper provides a study on technology for providing public etiquette services based on low power Bluetooth technology (BLE) and smartphone control techniques to limit and release based on BLE beacon.Â Â Â